Konsep Perkembangan Sosial Emosional Anak Usia Dini Di RA Tarbiyatussibyan Ploso Karangtengah Demak - Fitriya, Aulina; Indriani, Indah; Noor, Fu'ad Arif (Universitas Islam Negeri Sumatera Utara, 2022)
Socio-emotional development is one aspect of development that is very important for every child because it is one of the determining factors for his success in the future. Early childhood is a golden age for every aspect of development, including social and emotional aspects. Therefore, the process of child growth and development must always be considered so that it runs optimally. This study aims to determine and analyze the concept of social emotional development of early childhood in RA Tarbiyatussibyan Ploso Karangtengah Demak. This research is a qualitative descriptive research. Collecting data using interviews, observation and documentation. Technique of data analysis technique of triangulation of data. The findings show that teachers have made various efforts to develop social emotional early childhood at RA Tarbiyatussibyan Ploso Karangtengah Demak, such as: (1) paying attention, (2) introducing the form of emotions and their impact through stories, (3) providing a sense of security, comfort, and affection, (4) habituation of positive behavior at school, (5) giving reinforcement with praise and appreciation, (6) providing facilities to choose and actualize hobbies, and (7) establish communication with students.